2007
DOI: 10.1196/annals.1397.047
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Induces Apoptosis in Chemoresistant Cancer Cells via Modulation of AMPK Signaling Pathway

Abstract: Resveratrol has been reported to possess therapeutic effects for various cancers including colon cancers. In this article, the molecular basis of resveratrol with emphasis on its ability to control intracellular signaling cascades of adenosine monophosphate (AMP)-activated protein kinase (AMPK) responsible for inducing apoptosis in drug-resistant cancer cells was investigated. Recently, the evolutionarily conserved serine/threonine kinase, AMPK, emerges as a possible target molecule of cancer control. We have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 16 publications
9
92
0
Order By: Relevance
“…Specifically, we demonstrated that resveratrol turned on AMPK activity both in cell cultures and in vivo in mouse brain after oral dosing and that AMPK inhibition significantly impaired the effect of resveratrol on A␤ accumulation in cell lines and in primary neurons. The observation that resveratrol activates AMPK is in line with previous studies using cell line cultures and animal models (42,(45)(46)(47)(48)(49). For instance, it was shown that resveratrol administered orally through the diet can activate AMPK at the periphery in mouse liver (42).…”
Section: Discussionsupporting
confidence: 85%
“…Specifically, we demonstrated that resveratrol turned on AMPK activity both in cell cultures and in vivo in mouse brain after oral dosing and that AMPK inhibition significantly impaired the effect of resveratrol on A␤ accumulation in cell lines and in primary neurons. The observation that resveratrol activates AMPK is in line with previous studies using cell line cultures and animal models (42,(45)(46)(47)(48)(49). For instance, it was shown that resveratrol administered orally through the diet can activate AMPK at the periphery in mouse liver (42).…”
Section: Discussionsupporting
confidence: 85%
“…13,14) In addition, resveratrol, a polyphenolic natural product, 25) induces apoptosis in HT-29 cells via AMPK activation. 26) Our findings demonstrated that AglRhz is able to increase phosphorylation of AMPK and decrease cell viability in HT-29 cells (Figs. 1B, 2A, B).…”
Section: Discussionsupporting
confidence: 52%
“…The effects of metabolic stress such as hypoxia, caloric restriction, or muscle contraction on AMPK signaling in aging are equally equivocal with some studies reporting increased activation (169,379), while others have reported a reduction (349,408). Interestingly, resveratrol (3,5,4Ј-trihydroxystilbene), which extends the life span of organisms through Sir2, a conserved deacetylase, proposed to underlie the beneficial effects of caloric restriction, activates AMPK (121, 220,384,575). While recent studies suggest that the effect of Sir2 on longevity may have more to do with altered insulin and IGF-I signaling than AMPK (292), future studies examining longevity in AMPK null mice will be important.…”
Section: A Aging and Longevitymentioning
confidence: 99%
“…However, the mechanism(s) of action of these compounds has remained largely a mystery, limiting their therapeutic potential. Several recent studies have demonstrated that polyphenols such as resveratrol stimulate AMPK activity in a variety of cell types including liver (575), skeletal muscle (36, 384), neurons (121), and cancer (220). The activation of AMPK by resveratrol may be mediated by AMP as resveratrol inhibits the mitochondrial F1 ATPase (166).…”
Section: Polyphenols and Resveratrolmentioning
confidence: 99%